(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Global warming is the phenomenon of an increase in average air temperatures at the Earth’s surface over the past hundred years. Since the early 20th century, climate scientists have systematically collected detailed data on various weather conditions, such as temperature, precipitation, and storms, and studied their associated climate impacts, such as ocean currents and atmospheric chemistry. [2] These data indicate that the Earth’s climate has varied over almost every known time period since the geological past, and that the impacts of human activity have had an increasingly pronounced impact on the nature and the scale of modern climate change.